The Development of Ethnomathematics-Based Learning Tools in Ball Games to Improve Understanding of Permutation and Combination Concepts - Kinasih, Dewi; Sugilar; Ramdhani, Sendi (Jurnal Sains Sosio Humaniora, 2025)
This research aims to describe the development process, the quality of the development results, and the enhancement of students' conceptual understanding through the development of mathematics learning tools based on ethnomathematics using the bola bekel (a traditional ball game) activity. This study employs a Research and Development (R&D) design utilizing the ADDIE development model. The population of this study was students at SMAN 3, with the research sample consisting of eleventh-grade students. The resulting learning products from this R&D study include Lesson Plans (RPP) and Student Worksheets (LKPD). The findings of this development research are: 1) A detailed description of the systematic development of the learning product using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). 2) The quality of the developed product is categorized as good to very good, indicated by the results of validity, practicality, and effectiveness testing, which showed categories of very valid, practical-to-very practical, and effective, demonstrated by the increase in students' conceptual understanding. This increase is projected by the student passing rate on the Minimum Mastery Criteria (KKM) score, which rose significantly from a mere 9.09% to 78.8%. Based on the Wilcoxon test conducted, there is a significant influence from the use of ethnomathematics-based learning materials derived from the bola bekel game on students’ conceptual understanding of the Permutation and Combination subject matter. Referring to these research findings, it can be concluded that the development of ethnomathematics-based learning products utilizing the bola bekel game is proven valid, effective, and practical in enhancing students' conceptual understanding of Permutation and Combination.